Academic E-Mail Overload and the Burden of "Academic Spam". (20th January 2020) - Wood, Kelly E.; Krasowski, Matthew D.
This article presents an editorial perspective on the challenges associated with e-mail management for academic physicians. We include 2-week analysis of our own e-mails as illustrations of the e-mail volume and content. We discuss the contributors to high e-mail volumes, focusing especially on unsolicited e-mails from medical/scientific conferences and open-access journals (sometimes termed "academic spam emails"), as these e-mails comprise a significant volume and are targeted to physicians and scientists. Our 2-person sample is consistent with studies showing that journals that use mass e-mail advertising have low rates of inclusion in recognized journal databases/resources. Strategies for managing e-mail are discussed and include unsubscribing, blocking senders or domains, filtering e-mails, managing one's inbox, limiting e-mail access, and e-mail etiquette. Academic institutions should focus on decreasing the volume of unsolicited e-mails, fostering tools to manage e-mail overload, and educating physicians including trainees about e-mail practices, predatory journals, and scholarly database/resources.